Anticholinergic burden and health outcomes among older adults discharged from hospital: results from the CRIME study - Gutiérrez-Valencia, Marta; Martínez-Velilla, Nicolás; Vetrano, Davide Liborio; Corsonello, Andrea; Lattanzio, Fabrizia; Ladrón-Arana, Sergio; Onder, Graziano (European journal of clinical pharmacology, 2017)
Purpose The purpose of this study is to investigate whether there is an association between anticholinergic burden and mortality or rehospitalization in older adults discharged from hospital. Methods Prospective multicenter cohort study carried out with patients aged 65 and older discharged from seven acute care hospitals. The primary outcomes of the study were rehospitalization and mortality within 1 year after discharge. The study population was classified in three groups according to the anticholinergic exposure measured by the Anticholinergic Risk Scale (ARS) and Durán’s list at the time of hospital discharge: without risk (ARS/Durán = 0), low risk (ARS/Durán = 1), and high risk (ARS/Durán ≥ 2). Predictors of hospitalizations and mortality were examined using regression models adjusting for important covariates. Results The mean age of the 921 participants was 81.2 years (SD = 7.4 years). Prevalence of exposure to medications with anticholinergic activity ranged from 19.6% with ARS to 32.1% with Durán’s list. During the follow-up period, 30.4% of participants were hospitalized and 19.4% died. Multivariate regression analysis showed that low anticholinergic burden quantified according to Durán’s list was significantly associated with all-cause mortality (OR 1.69, 95% CI 1.02–2.82). This association was not present after adjustment when using ARS. No statistically significant association was found between anticholinergic burden and hospitalizations. Conclusions Taking medications with anticholinergic activity is associated with greater risk of mortality in older adults discharged from acute care hospitals. Strategies to reduce anticholinergic burden in vulnerable elders could be useful to improve health outcomes. Further research is required to assess the association between anticholinergic burden and hospitalizations in older patients.